Magnesium-aluminum-based intermediate plate, brazing plate and composite plate for controlled atmosphere brazing and preparation method thereof
By using a pre-embedded fluorine-containing flux layer and annealed partition layer in the Mg-containing aluminum alloy, the brazing performance problems caused by Mg element diffusion are solved, and efficient and controllable atmosphere brazing is achieved, ensuring the quality of welds and material strength.
Patent Information
- Application Number
- CN202411794595.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-09
AI Technical Summary
During the Mg-containing aluminum alloy, due to the strong affinity of Mg elements to oxygen, it is easy to form difficult-to-remove oxide films, resulting in deterioration of brazing performance. Commonly used flux reacts with Mg to form high melting point products, which fails and is difficult to perform efficient and controllable atmosphere brazing.
An embedded flux layer with fluorine-containing flux particles is used to form a partition layer between the core layer and the embedded flux layer through an annealing process to prevent Mg elements from diffusing to the surface, and the remaining flux film is used to assist in the brazing process.
It is realized efficiently and controllable atmosphere brazing without adding a barrier layer, ensuring the quality and material strength of the weld after brazing, with the weld length above 15mm and the tensile strength above 150MPa.
Smart Images

Figure CN119237862B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of magnesium-containing aluminum alloys, and in particular to a magnesium-containing aluminum-based intermediate plate, a brazing plate and a composite plate for controlled atmosphere brazing and a preparation method thereof. Background Art
[0002] The brazing performance of magnesium-containing aluminum alloys is poor. The difficulty lies mainly in the fact that the Mg element in the magnesium-containing aluminum alloy has a strong affinity for oxygen. When brazing is heated, it will diffuse to the surface and oxidize, forming a Mg-rich oxide film that is difficult to remove. When brazing aluminum alloys, the molten brazing material must wet the base material, so this oxide film must be removed.
[0003] Controlled atmosphere brazing technology refers to the technology of achieving brazing under certain atmosphere conditions. By adjusting the flow rate and content of nitrogen and / or argon in the atmosphere, the atmosphere conditions of the brazing process are made more stable and uniform, thereby improving the brazing quality. When the brazing atmosphere is a controlled atmosphere, due to the strong affinity of Mg element for oxygen, it will diffuse to the surface and oxidize when the brazing is heated, forming a large amount of Mg-rich oxide film and refractory products that are difficult to remove, which increases the difficulty of brazing.
[0004] More importantly, the Mg element will react with fluorine-based brazing fluxes. Taking the commonly used brazing flux KF-AlF3 for aluminum alloy brazing as an example, during the brazing process, the KF-AlF3 brazing flux reacts chemically with the Mg in the alloy to form high melting point products such as MgF2 and KMgF3, which reduces the effective components of the brazing flux, causing partial or complete failure of the brazing flux, and deteriorating the performance when brazing magnesium-containing aluminum alloys. Studies have shown that when the Mg content is greater than 0.3wt%, brazing with KF-AlF3 brazing flux becomes difficult.
[0005] Therefore, Mg-containing aluminum alloys are generally brazed by vacuum brazing. However, the vacuum brazing process is complicated and costly, and the vacuuming process greatly limits the capacity of mass production lines.
[0006] Currently, there is also a solution of adding a barrier layer to perform controlled atmosphere brazing on Mg-containing aluminum alloys, that is, adding a barrier layer between the core material layer and the skin layer to prevent the Mg element in the core material layer from diffusing to the surface. However, since the barrier layer needs to be extremely thick and cannot contain Mg elements, the addition of the barrier layer leads to a decrease in the total Mg content in the overall aluminum alloy. Under the condition of equal thickness, the strength of the overall aluminum alloy decreases.
[0007] Therefore, it is necessary to develop a process and product for producing a high-strength Mg-containing aluminum alloy capable of controlled atmosphere brazing. Summary of the invention
[0008] In order to solve the above technical problems, the present invention provides a magnesium-aluminum-based intermediate plate, a brazing plate and a composite plate for controlled atmosphere brazing and a preparation method thereof, which can solve the problem of reduced strength caused by the use of a barrier layer during controlled atmosphere brazing of Mg-containing aluminum alloys.
[0009] To achieve this object, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a magnesium-aluminum-based intermediate plate for controlled atmosphere brazing, the magnesium-aluminum-based intermediate plate comprising a core material layer and a brazing composite layer which are stacked; the brazing composite layer comprises a pre-embedded brazing flux layer and a filler layer, the pre-embedded brazing flux layer being arranged close to the core material layer; and the thickness of the pre-embedded brazing flux layer is ≥0.01 mm; the pre-embedded brazing flux layer is a filler alloy containing fluorine-containing brazing flux particles; the amount of fluorine-containing brazing flux particles added in the pre-embedded brazing flux layer is ≤15wt%; the core material layer is an aluminum-based alloy containing magnesium, wherein the alloy elements of the core material layer include, in terms of mass percentage: Mg, 0.3%~1.5%.
[0011] The present invention limits the thickness of the embedded flux layer in the intermediate product to at least 0.01 mm, because the annealing process needs to form a barrier layer of at least 5 μm thick to restrict the diffusion space of Mg during the brazing process; and the remaining thickness of the embedded flux layer after annealing is at least 1 times the thickness of the formed barrier layer to ensure that there is sufficient remaining embedded flux in the subsequent process to help the brazing proceed smoothly.
[0012] The thickness of the embedded flux layer in the present invention is ≥0.01 mm, for example, it can be 0.01 mm, 0.02 mm, 0.03 mm, 0.04 mm, 0.05 mm, 0.06 mm, 0.07 mm, 0.08 mm, 0.09 mm, 0.1 mm, 0.12 mm, 0.13 mm, 0.14 mm or 0.15 mm.
[0013] Specifically, the added amount of fluorine-containing flux particles in the pre-embedded flux layer is ≤15wt%, for example, it can be 5wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt% or 15wt%.
[0014] The upper limit of the amount of fluorine-containing flux particles added to the pre-embedded flux layer in the present invention cannot exceed 15wt%. A high flux content may cause difficulty in subsequent mechanical processing (such as hot rolling, compounding, etc.).
[0015] Specifically, the alloy elements of the core material layer include, by mass percentage: Mg, 0.3% to 1.5%, for example, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1.5%.
[0016] The content of Mg in the core material layer of the present invention is preferably within the above range, which can ensure the strength of the magnesium-aluminum-based composite plate on the one hand, and can better achieve controlled atmosphere brazing on the other hand. When the Mg content is low, the Mg content in the overall magnesium-aluminum-based composite plate decreases, resulting in insufficient overall strength. When the Mg content is high, the plasticity decreases, the formability decreases, and the corrosion resistance deteriorates. The relationship between the range of Mg content selection and the target strength is routinely adjusted by those skilled in the art.
[0017] Preferably, the fluorine-containing flux particles are made of inorganic materials.
[0018] Preferably, the alloy elements of the core material layer include, by mass percentage: Cu, 0.1% to 10%; Mn, 0.1% to 5%; Zn, 0.1% to 2%.
[0019] Among them, Cu, 0.1%~10%, for example, it can be 0.1%, 1.2%, 2.3%, 3.4%, 4.5%, 5.6%, 6.7%, 7.8%, 8.9% or 10%; Mn, 0.1%~5%, for example, it can be 0.1%, 0.7%, 1.2%, 1.8%, 2.3%, 2.9%, 3.4%, 4%, 4.5% or 5%; Zn, 0.1%~2%, for example, it can be 0.1%, 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8% or 2%.
[0020] Preferably, the thickness of the brazing composite layer accounts for ≥5% of the total thickness of the magnesium-aluminum-based intermediate plate, for example, it may be 5%, 7%, 10%, 12%, 15%, 16%, 17%, 18%, 19% or 20%.
[0021] The thickness of the brazing composite layer is limited to a minimum proportion of 5% of the total thickness because it is necessary to ensure that the brazing filler metal is sufficiently matched to obtain a full and qualified brazing joint.
[0022] Preferably, the thickness of the core material layer accounts for ≥ 80% of the total thickness of the magnesium-aluminum-based intermediate plate, for example, it may be 80%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89% or 90%.
[0023] In order to achieve high strength and meet the performance requirements of aluminum materials, the minimum core material thickness should account for ≥ 80% of the total thickness. When the core material thickness is guaranteed to be above 80%, the subsequent loss of Mg element will basically not affect the acquisition of target strength.
[0024] Preferably, the total thickness of the magnesium-aluminum-based intermediate plate is ≥0.1 mm, for example, it can be 0.1 mm, 0.12 mm, 0.13 mm, 0.14 mm, 0.15 mm, 0.16 mm, 0.18 mm, 0.2 mm, 0.22 mm, 0.23 mm, 0.25 mm, 0.28 mm, 0.3 mm, 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 3.5 mm or 4 mm, etc.
[0025] Preferably, the material of the filler layer is filler alloy.
[0026] Preferably, the filler alloy is a 4-series aluminum-silicon alloy.
[0027] Preferably, the Si content in the filler alloy is 8-12wt% by mass percentage, for example, it may be 8wt%, 8.5wt%, 8.9wt%, 9.4wt%, 9.8wt%, 10.3wt%, 10.7wt%, 11.2wt%, 11.6wt% or 12wt%.
[0028] The present invention also provides a method for preparing the magnesium-aluminum-based intermediate plate for controlled atmosphere brazing, the method comprising the following steps:
[0029] (1) preparing a core material layer slab and a brazing composite layer, wherein the brazing composite layer includes a pre-embedded brazing flux layer and a filler layer, and hot rolling them to a target thickness according to a proportion;
[0030] (2) The core material layer and the brazing composite layer are stacked, wherein the embedded brazing flux layer is arranged close to the core material layer, and hot-rolled composite is performed, and then cold-rolled to obtain a magnesium-aluminum-based intermediate plate of a desired thickness.
[0031] Preferably, the hot rolling temperature is 430-480°C, for example, it may be 430°C, 436°C, 442°C, 447°C, 453°C, 458°C, 464°C, 469°C, 475°C or 480°C.
[0032] Preferably, the cold rolling reduction is ≥50%, for example, it may be 50%, 52%, 53%, 54%, 58%, 60%, 62%, 65%, 68%, 70%, 72% or 75%, etc.
[0033] Preferably, the magnesium-aluminum-based intermediate plate of the required thickness has a thickness of 0.1-3.5 mm, for example, 0.1 mm, 0.5 mm, 0.8 mm, 1.1 mm, 1.4 mm, 1.8 mm, 2.1 mm, 2.4 mm, 2.7 mm, 3 mm, 3.2 mm or 3.5 mm.
[0034] In a second aspect, the present invention provides a method for preparing a magnesium-aluminum-based brazing plate, wherein the magnesium-aluminum-based intermediate plate for controlled atmosphere brazing described in the first aspect is annealed to obtain a magnesium-aluminum-based brazing plate.
[0035] The present invention anneals the intermediate product. Under the annealing environment, Mg in the core material diffuses to the pre-embedded flux layer and reacts with the fluorine-based flux particles in the layer to form a barrier layer. The barrier layer can absorb the Mg element diffused from the core material layer during annealing and brazing, which is manifested as continuous growth of the barrier layer, thereby preventing the Mg element from diffusing to the surface.
[0036] The annealing temperature and time should be adjusted so that the thickness of the barrier layer between the core material layer and the pre-embedded flux layer is within the target range, so as to obtain the magnesium-containing high-strength composite aluminum plate suitable for controlled atmosphere brazing. The target thickness of the barrier layer meets 5 μm or more.
[0037] Preferably, the annealing temperature is 200-450°C, for example, it can be 200°C, 237°C, 284°C, 300°C, 317°C, 334°C, 367°C, 384°C, 422°C or 450°C, and the time is 0.25-4h, for example, it can be 0.25h, 0.5h, 0.8h, 1.1h, 1.4h, 1.7h, 2.2h, 2.8h, 3.4h or 4h, etc.
[0038] The present invention should select a suitable annealing process window to obtain the thickness of the barrier layer within the target range. The thickness of the barrier layer obtained under different annealing processes is different, and the thickness of the barrier layer affects the final brazing quality. The higher the temperature, the thicker the barrier layer, and the longer the time, the thicker the barrier layer. Under the conditions of different Mg content and the content of brazing flux in the pre-embedded brazing flux layer, and the thickness of the pre-embedded brazing flux layer, the appropriate annealing temperature and annealing time should be matched to make the thickness of the barrier layer within the target range. When the thickness of the barrier layer after annealing meets the requirements, the weld length of the brazing T-type test of the material is at least 15 mm.
[0039] In a third aspect, the present invention provides a magnesium-aluminum-based brazing plate, wherein the magnesium-aluminum-based brazing plate is prepared by the method for preparing the magnesium-aluminum-based brazing plate described in the second aspect.
[0040] Preferably, a barrier layer is provided on one side of the pre-embedded flux layer close to the core material layer, and the barrier layer contains KMgF3.
[0041] Preferably, the thickness of the isolation layer is ≥5 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm or 14 μm, etc., preferably the thickness is ≥6 μm, and more preferably the thickness is ≥9 μm.
[0042] During the annealing pretreatment process, the Mg element reacts with the F / K in the pre-embedded flux layer to generate a bright reactant layer in the SEM scan. The Mg element in the magnesium-aluminum alloy is highly diffusive and has a high affinity for oxygen. When brazing is heated, it diffuses to the surface and oxidizes to form a Mg-rich oxide film that is difficult to remove. This reactant layer formed during the annealing pretreatment plays a huge role in the brazing process. Studies have found that when this reactant layer reaches a certain thickness, it can restrict the diffusion space of Mg during the brazing process. During brazing, as the temperature rises, the isolation layer slowly thickens and absorbs the Mg element in the low Mg area, preventing it from diffusing to the surface, and it forms an isolation layer that blocks the diffusion of Mg to the surface. In the process of the continuous growth of the isolation layer, the brazing has been completed. At this time, the Mg atoms have not diffused to the surface of the leather material on a large scale, and there is no opportunity to form a Mg-rich oxide film on the surface of the leather material.
[0043] At the same time, the remaining brazing flux adjacent to the embedded brazing flux layer and the filler layer that has not yet reacted with Mg begins to play a role in breaking the film, helping the skin material to melt and complete brazing, effectively improving the quality and success rate of Mg-containing aluminum-based brazing plates, and solving the problem that Mg-containing aluminum-based brazing plates cannot be brazed in a controlled atmosphere. The material's post-weld strength can reach up to 192MPa, with good welding quality, full welds and a high success rate.
[0044] Preferably, the upper limit of the thickness of the isolation layer is half of the thickness of the pre-embedded flux layer.
[0045] During the annealing process, the insulation layer is produced by the reaction of the core material layer and the brazing agent in the pre-embedded brazing agent layer. In the brazing process, the growth of the insulation layer still causes a certain amount of brazing agent to be consumed. The brazing process also requires a sufficient amount of brazing agent to break the oxide film and ensure the brazing effect. Therefore, in order to control the consumption of brazing agent by the insulation layer within a controllable range, the thickness of the insulation layer needs to be limited to half the thickness of the pre-embedded brazing agent layer.
[0046] In a fourth aspect, the present invention provides a method for brazing a magnesium-aluminum-based composite plate, wherein the brazing preparation method uses the magnesium-aluminum-based brazing plate described in the third aspect for brazing, or uses the magnesium-aluminum-based brazing plate prepared by the method for preparing the magnesium-aluminum-based brazing plate described in the second aspect for brazing.
[0047] Preferably, the brazing preparation method comprises: laminating a magnesium-aluminum-based brazing plate with a skin layer, arranging the brazing composite layer close to the skin layer, and brazing to form the magnesium-aluminum-based composite plate;
[0048] Preferably, the brazing temperature is 577~630℃, for example, it can be 577℃, 583℃, 589℃, 595℃, 601℃, 607℃, 613℃, 619℃, 625℃ or 630℃, and the time is 1~30min, for example, it can be 1min, 5min, 8min, 11min, 14min, 18min, 21min, 24min, 27min or 30min, etc.
[0049] During the brazing process, the Mg in the core material layer will continue to diffuse into the insulation layer, and the insulation layer will continue to absorb the Mg in the core material layer, so that the thickness of the insulation layer will gradually increase. The diffusion of the Mg element is related to the temperature and time of brazing. The brazing temperature is preferably within the above range, which can ensure that the insulation layer continues to grow during the brazing process, but will not grow excessively to the skin layer, and also has a better brazing effect.
[0050] Preferably, during the brazing process, the thickness of the isolation layer gradually increases.
[0051] In a fifth aspect, the present invention provides a magnesium-aluminum-based composite plate, wherein the magnesium-aluminum-based composite plate is prepared by the brazing preparation method of the magnesium-aluminum-based composite plate described in the fourth aspect.
[0052] The magnesium-aluminum-based composite plate provided in the fifth aspect of the present invention can not only be brazed using controlled atmosphere brazing, but also has the advantage of high strength.
[0053] Compared with the prior art, the present invention has at least the following beneficial effects:
[0054] The magnesium-aluminum-based intermediate plate for controlled atmosphere brazing provided by the present invention correlates the thickness of the embedded flux layer, the content of fluorine-containing flux particles in the embedded flux layer, and the Mg content in the core material layer, and combines the annealing process to form a barrier layer in the magnesium-aluminum-based brazing plate formed after annealing. The barrier layer can prevent the Mg element from diffusing into the cortex during the controlled atmosphere brazing process. The Mg content on the surface of the magnesium-aluminum-based brazing plate sample after simulated brazing is less than 10wt%, and the weld length of the magnesium-aluminum-based composite plate measured under the T-type experiment is high, the weld length is more than 15mm, and the tensile strength is more than 150MPa, the strength is high, and the application prospect is broad. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 (a) is a SEM image of the magnesium-aluminum-based intermediate plate ZA1 in Example 1 of the present invention.
[0056] Figure 1 (b) corresponds to the present invention Figure 1 Mg element distribution map of EDS surface scanning in (a).
[0057] Figure 1(c) and Figure 1 (d) are the Mg element distribution diagram and element analysis data diagram of the EDS surface scan of the Mg-containing aluminum-based brazing plate QA1.
[0058] In the figure, 1-filling layer; 2-embedded flux layer; 3-core material layer. DETAILED DESCRIPTION
[0059] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0060] Core layer
[0061] The core material layer XA1 is an aluminum-based alloy containing magnesium, and includes Mg: 0.8%, Cu: 1.2%, Mn: 0.5%, and Zn: 0.2% in terms of mass percentage.
[0062] The core material layer XA2 is an aluminum-based alloy containing magnesium, and in terms of mass percentage, includes Mg: 0.3%, Cu: 0.1%, Mn: 0.1%, and Zn: 0.1%.
[0063] The core material layer XA3 is an aluminum-based alloy containing magnesium, and includes Mg: 1.5%, Cu: 10%, Mn: 5%, and Zn: 2% in terms of mass percentage.
[0064] Pre-embedded flux layer
[0065] The pre-embedded flux layer MA1 is a filler alloy containing fluorine-containing flux particles, wherein the fluorine-containing flux particles are KAl4F with a mass percentage of 5wt%, and the grade of the filler alloy is AA4045.
[0066] The pre-embedded flux layer MA2 is a filler alloy containing fluorine-containing flux particles, wherein the fluorine-containing flux particles are KAl4F with a mass percentage of 15wt%, and the grade of the filler alloy is AA4343.
[0067] The pre-embedded flux layer MA3 is a filler alloy containing fluorine-containing flux particles, wherein the fluorine-containing flux particles are KAl4F with a mass percentage of 10wt%, and the grade of the filler alloy is AA4045.
[0068] The pre-embedded flux layer MD1 is a filler alloy containing fluorine-containing flux particles, wherein the fluorine-containing flux particles are KAl4F with a mass percentage of 18wt%, and the grade of the filler alloy is AA4045.
[0069] Aluminum-based intermediate plates containing magnesium for controlled atmosphere brazing
[0070] Exemplarily, the method for preparing the following magnesium-aluminum-based intermediate plate comprises the following steps:
[0071] (1) preparing a core material layer blank and a brazing composite layer, wherein the brazing composite layer includes a pre-embedded brazing flux layer and a filler layer, and preheating and hot rolling them at 430-480° C. in proportion to a target thickness; the hot rolling preheating temperature of the present invention is 480° C.
[0072] (2) The core material layer and the brazing composite layer are stacked, wherein the pre-embedded brazing flux layer is arranged close to the core material layer, and hot-rolled composite is performed, and then cold-rolled, with a cold-rolling reduction of ≥50%, to obtain a magnesium-aluminum-based intermediate plate of a desired thickness. The cold-rolling reduction of the present invention is 80%.
[0073] The specific magnesium-containing aluminum-based intermediate plate is described in detail below.
[0074] Magnesium-aluminum-based intermediate plate ZA1: The magnesium-aluminum-based intermediate plate includes a core material layer and a brazing composite layer which are stacked; the brazing composite layer includes a pre-embedded brazing flux layer and a filler layer, and the pre-embedded brazing flux layer is arranged close to the core material layer; the pre-embedded brazing flux layer is a pre-embedded brazing flux layer MA1; the thickness of the pre-embedded brazing flux layer is 0.036 mm, accounting for 6% of the total thickness of the magnesium-aluminum-based intermediate plate; the thickness of the brazing composite layer accounts for 10% of the total thickness of the magnesium-aluminum-based intermediate plate; the core material layer is a core material layer XA1. The thickness of the core material layer accounts for 90% of the total thickness of the magnesium-aluminum-based intermediate plate; the total thickness of the magnesium-aluminum-based intermediate plate is 0.6 mm.
[0075] Magnesium-aluminum-based intermediate plate ZA2: The magnesium-aluminum-based intermediate plate includes a core material layer and a brazing composite layer arranged in layers; the brazing composite layer includes a pre-embedded flux layer and a filler layer, and the pre-embedded flux layer is arranged close to the core material layer; the pre-embedded flux layer is a pre-embedded flux layer MA2; the thickness of the pre-embedded flux layer is 0.01 mm, accounting for 5% of the total thickness of the magnesium-aluminum-based intermediate plate; the thickness of the brazing composite layer accounts for 15% of the total thickness of the magnesium-aluminum-based intermediate plate; the core material layer is a core material layer XA2. The thickness of the core material layer accounts for 85% of the total thickness of the magnesium-aluminum-based intermediate plate; the total thickness of the magnesium-aluminum-based intermediate plate is 0.2 mm.
[0076] Magnesium-aluminum-based intermediate plate ZA3: The magnesium-aluminum-based intermediate plate includes a core material layer and a brazing composite layer arranged in layers; the brazing composite layer includes a pre-embedded brazing flux layer and a filler layer, and the pre-embedded brazing flux layer is arranged close to the core material layer; the pre-embedded brazing flux layer is a pre-embedded brazing flux layer MA3; the thickness of the pre-embedded brazing flux layer is 0.35 mm, accounting for 10% of the total thickness of the magnesium-aluminum-based intermediate plate; the thickness of the brazing composite layer accounts for 20% of the total thickness of the magnesium-aluminum-based intermediate plate; the core material layer is a core material layer XA3. The thickness of the core material layer accounts for 80% of the total thickness of the magnesium-aluminum-based intermediate plate; the total thickness of the magnesium-aluminum-based intermediate plate is 3.5 mm.
[0077] Magnesium-aluminum-based intermediate plate ZD1: The magnesium-aluminum-based intermediate plate is different from the magnesium-aluminum-based intermediate plate ZA1 only in that the pre-embedded flux layer is the pre-embedded flux layer MD1, and the rest is the same as the magnesium-aluminum-based intermediate plate ZA1. The pre-embedded flux layer of the magnesium-aluminum-based intermediate plate ZD1 failed to form during the preparation process, and cracking was serious, so the magnesium-aluminum-based brazing plate could not be produced.
[0078] Test Method
[0079] 1. Measurement method of thickness of each layer of magnesium-aluminum-based intermediate plate:
[0080] The cross-sections of the various layers of the magnesium-aluminum-based intermediate plate will show different morphologies in the scanning electron microscope image. Usually, a scanning electron microscope (model zeiss sigma 300) can be used to measure the thickness of each layer of the intermediate plate. The thickness data can be measured using the AZTEC analysis software (version: version 5.0) equipped with the scanning electron microscope.
[0081] 2. Element content of each layer of magnesium-aluminum-based intermediate plate:
[0082] The element content of each layer of the magnesium-aluminum-based intermediate plate was determined by a scanning electron microscope (model zeiss sigma 300) coupled with an EDS probe (model OXFORD ULTIM MAX 65). The mass concentration of the alloy elements scanned at each layer was read using the AZTEC analysis software (version: version 5.0) equipped with the scanning electron microscope.
[0083] Magnesium-aluminum-based brazing sheet
[0084] Example 1
[0085] Magnesium-aluminum-based brazing plate QA1: The magnesium-aluminum-based intermediate plate ZA1 is annealed at a temperature of 330°C for 1 hour to obtain the magnesium-aluminum-based brazing plate; wherein, a barrier layer is provided on one side of the embedded flux layer close to the core material layer, the barrier layer contains KMgF3, and the thickness of the barrier layer is 7μm.
[0086] Example 2
[0087] Mg-aluminum-based brazing plate QA2: The only difference from Mg-aluminum-based brazing plate QA1 is that the annealing time is 0.5 h, the thickness of the obtained isolation layer is 5.2 μm, and the rest is the same as Mg-aluminum-based brazing plate QA1.
[0088] Example 3
[0089] Mg-aluminum-based brazing plate QA3: The only difference from Mg-aluminum-based brazing plate QA1 is that the annealing time is 1.5 h, the thickness of the obtained isolation layer is 8.2 μm, and the rest is the same as Mg-aluminum-based brazing plate QA1.
[0090] Example 4
[0091] Mg-aluminum-based brazing plate QA4: The only difference from Mg-aluminum-based brazing plate QA1 is that the annealing time is 2h and the thickness of the obtained isolation layer is 10.3μm. The rest is the same as Mg-aluminum-based brazing plate QA1.
[0092] Example 5
[0093] Mg-aluminum-based brazing plate QA5: The only difference from Mg-aluminum-based brazing plate QA1 is that the annealing time is 2.5h and the thickness of the obtained insulation layer is 12.6μm. The rest is the same as Mg-aluminum-based brazing plate QA1.
[0094] Example 6
[0095] Mg-aluminum-based brazing plate QA6: The only difference from Mg-aluminum-based brazing plate QA1 is that the annealing time is 4h and the thickness of the obtained insulation layer is 17.2μm. The rest is the same as Mg-aluminum-based brazing plate QA1.
[0096] Example 7
[0097] Mg-aluminum-based brazing sheet QA7: The only difference from Mg-aluminum-based brazing sheet QA1 is that the annealing temperature is 250°C and the thickness of the obtained isolation layer is 5.5 μm. The rest is the same as Mg-aluminum-based brazing sheet QA1.
[0098] Example 8
[0099] Mg-aluminum-based brazing plate QA8: The only difference from Mg-aluminum-based brazing plate QA1 is that the annealing temperature is 280°C and the thickness of the obtained isolation layer is 7.3 μm. The rest is the same as Mg-aluminum-based brazing plate QA1.
[0100] Example 9
[0101] Mg-aluminum-based brazing sheet QA9: The only difference from Mg-aluminum-based brazing sheet QA1 is that the annealing temperature is 300°C and the thickness of the obtained isolation layer is 9 μm. The rest is the same as Mg-aluminum-based brazing sheet QA1.
[0102] Example 10
[0103] Mg-aluminum-based brazing sheet QA10: The only difference from Mg-aluminum-based brazing sheet QA1 is that the annealing temperature is 350°C and the thickness of the obtained isolation layer is 11.2 μm. The rest is the same as Mg-aluminum-based brazing sheet QA1.
[0104] Embodiment 11
[0105] Mg-aluminum-based brazing sheet QA11: The only difference from Mg-aluminum-based brazing sheet QA1 is that the annealing temperature is 400°C and the thickness of the obtained isolation layer is 15μm. The rest is the same as Mg-aluminum-based brazing sheet QA1.
[0106] Example 12
[0107] Mg-aluminum-based brazing sheet QA12: The only difference from Mg-aluminum-based brazing sheet QA1 is that the annealing temperature is 200°C and the thickness of the obtained isolation layer is 5.1 μm. The rest is the same as Mg-aluminum-based brazing sheet QA1.
[0108] Embodiment 13
[0109] Mg-aluminum-based brazing plate QA13: The only difference from Mg-aluminum-based brazing plate QA1 is that the annealing temperature is 450°C and the thickness of the obtained isolation layer is 17.8μm. The rest is the same as Mg-aluminum-based brazing plate QA1.
[0110] Embodiment 14
[0111] Magnesium-aluminum-based brazing plate QA14: The magnesium-aluminum-based intermediate plate ZA2 is annealed at a temperature of 300°C for 0.25h to obtain the magnesium-aluminum-based brazing plate; wherein, a barrier layer is provided on one side of the embedded flux layer close to the core material layer, the barrier layer contains KMgF3, and the thickness of the barrier layer is 5μm.
[0112] Embodiment 15
[0113] Magnesium-aluminum-based brazing plate QA15: The magnesium-aluminum-based intermediate plate ZA3 is annealed at a temperature of 330°C for 1h to obtain the magnesium-aluminum-based brazing plate; wherein, a barrier layer is provided on one side of the embedded flux layer close to the core material layer, the barrier layer contains KMgF3, and the thickness of the barrier layer is 76μm.
[0114] Comparative Example 1
[0115] Mg-aluminum-based brazing plate QD1: The only difference from Mg-aluminum-based brazing plate QA1 is that the annealing time is 0.1 h, the thickness of the obtained isolation layer is 3.6 μm, and the rest is the same as Mg-aluminum-based brazing plate QA1.
[0116] Comparative Example 2
[0117] Mg-aluminum-based brazing plate QD2: The only difference from Mg-aluminum-based brazing plate QA1 is that the annealing time is 5h and the thickness of the obtained isolation layer is 18.6μm. The rest is the same as Mg-aluminum-based brazing plate QA1. The thickness of the isolation layer exceeds half the thickness of the pre-embedded flux layer of the Mg-aluminum-based intermediate plate.
[0118] Comparative Example 3
[0119] Mg-aluminum-based brazing plate QD3: The only difference from Mg-aluminum-based brazing plate QA1 is that the annealing temperature is 180°C and the thickness of the obtained isolation layer is 4.5 μm. The rest is the same as Mg-aluminum-based brazing plate QA1.
[0120] Comparative Example 4
[0121] Mg-aluminum-based brazing sheet QD4: The only difference from Mg-aluminum-based brazing sheet QA1 is that the annealing temperature is 480°C and the thickness of the obtained isolation layer is 19.2μm. The rest is the same as Mg-aluminum-based brazing sheet QA1. The thickness of the isolation layer exceeds half the thickness of the pre-embedded flux layer of the Mg-aluminum-based intermediate plate.
[0122] Test Method
[0123] 1. Measurement method of the thickness of the insulation layer of magnesium-aluminum-based brazing plate:
[0124] Since the barrier layer of the magnesium-aluminum-based brazing plate cannot show morphological differences under a scanning electron microscope, the present invention adopts the characteristics of the Mg element content distribution of the barrier layer and uses EPMA (model Shimadzu 1720) to measure the thickness of the barrier layer formed in the magnesium-aluminum-based brazing plate.
[0125] 2. Diffusion capacity evaluation: Determine the Mg content on the surface of the sample after simulated brazing;
[0126] The surface of the magnesium-aluminum-based brazing plate sample after simulated brazing was scanned using a scanning electron microscope (zeiss sigma 300) and an EDS probe (OXFORD ULTIM MAX 65). The mass concentration of the Mg element obtained by the surface scan was read using the AZTEC analysis software (version 5.0) equipped with the scanning electron microscope.
[0127] Testing the brazing performance and post-weld tensile strength of magnesium-aluminum-based brazing plates
[0128] 1. Brazing performance of magnesium-containing aluminum-based brazing sheet (T-type brazing test): The magnesium-containing aluminum-based brazing sheet sample prepared by the present invention was processed into a specification size of 23mm×58mm, and placed on the surface of a 3003 alloy with a thickness×width×length of 2mm×25mm×60mm. Then, a piece of 3003 alloy with a thickness×width×length of 1mm×25mm×55mm was vertically placed on the upper part of the single-layer brazable aluminum alloy material, and the other end was padded and fixed with a steel wire with a diameter of 1mm, so that The distance from the contact point of the vertical 3003 alloy and the magnesium-aluminum-based brazing plate sample to the steel wire is kept at 50 mm, and a tooling sample with a cross section like an inverted "T" is made, referred to as a T-type sample; the T-type sample is placed in a continuous furnace (CAB furnace) protected by a nitrogen atmosphere for brazing, and the target brazing temperature and time conditions are set. The belt speed is 350 mm / min, and the formation of the weld is observed and counted (the construction of the T-type sample refers to CN115927923A), and the weld length is measured, recorded as d mm.
[0129] 2. Tensile strength after welding: The tensile strength test of the magnesium-aluminum-based brazing plate samples after simulated brazing adopts the standard method of GB / T228.1-2021 "Room temperature tensile properties part 1: test method", and the tensile strength of the magnesium-aluminum-based brazing plate samples after simulated brazing is determined by Zwick universal testing machine.
[0130] The brazing parameters and test results of Examples 1 to 13 and Comparative Examples 1 to 4 are shown in Table 1.
[0131] Table 1
[0132]
[0133] Taking Example 1 as an example, the aluminum alloy plates at various stages in Example 1 were tested. Figure 1 As shown, Figure 1 (a) is the SEM image of the magnesium-aluminum-based intermediate plate ZA1. Figure 1 As can be seen in (a), the magnesium-aluminum-based intermediate plate includes a core material layer 3 and a brazing composite layer which are stacked; the brazing composite layer includes a pre-embedded brazing flux layer 2 and a filler layer 1, and the pre-embedded brazing flux layer 2 is arranged close to the core material layer 3. Figure 1 (b) Correspondence Figure 1 (a) Mg element distribution diagram of EDS surface scanning, where the yellow pixel highlights represent Mg elements. Figure 1 (b) It can be seen that before annealing, the pre-embedded flux layer 2 and the filler layer 1 in the magnesium-aluminum-based intermediate plate do not contain Mg element. Figure 1 (c) is the Mg element distribution diagram of the EDS surface scan after the Mg-aluminum-based intermediate plate ZA1 is annealed to become the Mg-aluminum-based brazing plate QA1. Figure 1(c) An obvious yellow bright line can be seen, which is the isolation layer after annealing. EDS is performed on the bright yellow in the area to detect the main components of the isolation layer, and the main component results of the isolation layer are shown in Figure (d). From the scanning results, it can be seen that the main compound formula of the isolation layer is KMgF3.
[0134] From Table 1, we can see the following points:
[0135] (1) It can be seen from Examples 1 to 15 that the magnesium-aluminum-based intermediate plate provided by the present invention can be brazed in a controlled atmosphere without adding an additional barrier layer after annealing through the annealing process window, and the weld length obtained by the post-welding T-type test is long, the surface Mg content is less than 10wt%, and the tensile strength is above 150MPa;
[0136] At the same time, it can be seen from Examples 1 to 13 that the annealing temperature and annealing time have a significant effect on the thickness of the barrier layer. The present invention preferably selects a suitable annealing temperature and annealing time to match, and can obtain a barrier layer greater than or equal to 5 μm and not exceeding half the thickness of the pre-embedded flux layer of the magnesium-aluminum-based intermediate plate. The barrier layer in this thickness range will continue to grow during the subsequent brazing process and prevent the Mg element from diffusing to the surface.
[0137] By comparing Examples 1 to 13, it can be seen that the thickness of the isolation layer in Examples 2, 7 and 12 is less than 6 μm, and the barrier effect thereof on the Mg element is lower than that in Examples 1, 3 to 6, 8 to 11 and 13. Furthermore, the thickness of the isolation layer in Examples 1, 3 and 8 is less than 9 μm, and the barrier effect thereof on the Mg element is lower than that in Examples 4 to 6, 9 to 11 and 13, and the brazing performance of Examples 4 to 6, 9 to 11 and 13 is better than that of Examples 1, 3 and 8. Therefore, the thickness of the isolation layer is preferably ≥ 6 μm, and the thickness is more preferably ≥ 9 μm.
[0138] (2) It can be seen from Example 1 and Comparative Examples 1 to 4 that when the annealing temperature and time are not within the preferred range, the thickness of the barrier layer does not increase enough or is too thick. When the thickness of the barrier layer is less than 5 μm, the barrier layer cannot prevent the Mg element in the core material layer from diffusing to the surface during the brazing process (Example 1, Comparative Example 1 and Comparative Example 3), resulting in an increase in the Mg content on the surface of the sample after simulated brazing in Comparative Example 1 and Comparative Example 3, and poor T-type test results. When the thickness of the barrier layer formed in Comparative Example 2 and Comparative Example 4 exceeds half of the thickness of the pre-embedded brazing flux layer of the Mg-aluminum-based intermediate plate, too much brazing flux is consumed, and the T-type test results are poor. This shows that the present invention controls the annealing temperature and time within a reasonable range to obtain a barrier layer greater than or equal to 5 μm and not exceeding half of the thickness of the pre-embedded brazing flux layer of the Mg-aluminum-based intermediate plate, and can achieve controlled atmosphere brazing of Mg-containing composite aluminum alloys without a barrier layer.
[0139] The present invention illustrates the detailed features of the present invention through the above embodiments, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, equivalent replacement of the technical features selected by the present invention, addition of auxiliary technical features, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A magnesium-aluminum-based intermediate plate for controlled atmosphere brazing, characterized in that: The magnesium-aluminum-based intermediate plate comprises a core material layer and a brazing composite layer which are stacked; The brazing composite layer comprises a pre-embedded brazing flux layer and a filler layer, wherein the pre-embedded brazing flux layer is arranged close to the core material layer; The thickness of the pre-embedded flux layer is ≥0.01 mm; The pre-embedded flux layer is a filler alloy containing fluorine-based flux particles; The amount of fluorine-containing flux particles added to the pre-embedded flux layer is ≤15wt%; The core material layer is an aluminum-based alloy containing magnesium, wherein the alloy elements of the core material layer include, by mass percentage: Mg, 0.3% to 1.5%; After annealing, the magnesium-aluminum-based intermediate plate is annealed to obtain a magnesium-aluminum-based brazing plate. The magnesium-aluminum-based brazing plate has a barrier layer on one side of the embedded flux layer close to the core material layer. The barrier layer contains KMgF3 and has a thickness of ≥5 μm.
2. The magnesium-aluminum-based intermediate plate according to claim 1, characterized in that: The ratio of the thickness of the brazing composite layer to the total thickness of the magnesium-aluminum-based intermediate plate is ≥5%.
3. The magnesium-aluminum-based intermediate plate according to claim 1 or 2, characterized in that: The thickness of the core material layer accounts for ≥ 80% of the total thickness of the magnesium-aluminum-based intermediate plate; And / or, the total thickness of the magnesium-aluminum-based intermediate plate is ≥0.1 mm.
4. A method for preparing a magnesium-aluminum-based brazing sheet, characterized in that: The preparation method anneals the magnesium-aluminum-based intermediate plate for controlled atmosphere brazing according to any one of claims 1 to 3 to obtain a magnesium-aluminum-based brazing plate.
5. The preparation method according to claim 4, characterized in that: The annealing temperature is 200-450° C., and the annealing time is 0.25-4 hours.
6. A magnesium-aluminum-based brazing plate, characterized in that: The magnesium-aluminum-based brazing sheet is prepared by the method for preparing the magnesium-aluminum-based brazing sheet according to claim 4 or 5; A barrier layer is provided on one side of the pre-embedded flux layer close to the core material layer. The barrier layer contains KMgF3 and has a thickness of ≥5 μm.
7. The magnesium-containing aluminum-based brazing sheet according to claim 6, characterized in that: The thickness of the barrier layer is ≥6 μm, and / or the upper limit of the thickness of the barrier layer is half of the thickness of the pre-embedded flux layer of the magnesium-aluminum-based intermediate plate.
8. A brazing preparation method for a magnesium-aluminum composite plate, characterized in that: The brazing preparation method adopts the magnesium-aluminum-based brazing plate according to claim 6 or 7 for brazing, or adopts the magnesium-aluminum-based brazing plate prepared by the preparation method of the magnesium-aluminum-based brazing plate according to claim 4 or 5 for brazing.
9. The preparation method according to claim 8, characterized in that: The brazing preparation method comprises: laminating a magnesium-aluminum-based brazing plate and a skin layer, arranging the brazing composite layer close to the skin layer, and brazing to form the magnesium-aluminum-based composite plate; The brazing temperature is 577-630°C and the brazing time is 1-30 minutes; During the brazing process, the thickness of the isolation layer gradually increases.
10. A magnesium-aluminum-based composite plate, characterized in that: The magnesium-aluminum-based composite plate is prepared by the brazing preparation method of the magnesium-aluminum-based composite plate according to claim 9.
Citation Information
Patent Citations
Single-layer brazed aluminum alloy material and manufacturing method thereof
CN115927923A
Aluminum alloy composite material for fuel cell radiator and preparation method of aluminum alloy composite material
CN117301647A
Aluminum alloy brazing composite material and preparation method and application thereof
CN118616961A
Aluminum alloy brazing sheet and method for manufacturing the same, and method for brazing aluminum-made heat exchanger
JP2013146755A